Evaluating Community Pharmacist Provided Short Education Program to Improve Clinical Status of Selected Asthmatic Patients - Abbas Khazaal Okab, Ali Mohammed Hadi, Ied Al_Sadoon, Mudher Al-Khairalla, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Incorrect inhaler usage is very common issue that leads to poorly managed asthma. Clinical pharmacist enhanced patient education is critical in reducing such errors. Education on inhaler technique is one area where pharmacists may significantly impact on asthma therapy and improvement in clinical features. Aim: This study aim to evaluate the efficacy of a pharmacist-delivered education program for improving patients' inhaler technique and clinical outcomes. Patients and Methods: This prospective cohort trial included 51 individuals with asthma, divided up between an intervention group of 26 participants who were subjected to pharmacist intervention as well as a control group of 25 participants. MDI and turbuhaler users were gathered to participate in the study from five community pharmacies in different areas of the Thi-Qar province (Nasirriya, Suq Al-Shoyookh, and Al Eslaah cities). Basic asthma control and spirometry parameters were evaluated using standardized questionnaire of asthma control test and spirometer respectively. Patients in intervention group were taught how to properly use their inhalers using a combination including demonstrations and re-demonstrations counselling with aid of advices leaflet. After one month for both groups, clinical outcomes (asthma control and spirometry) were reassessed and comparisons were made. Results: A total of 51 patients were involved, with 35 using a turbuhaler and 16 using an MDI. At first session of assessment for all participants, a low asthma control and low median value of FEV1/FVC ratio were recording. After intervention, the median values for asthma control test and all pulmonary parameters was increased significantly (for ACT of 18.5 to 21, p=0.000, for PEF of 2.2 to 2.8, p=0.001, for FEV1 of 1.6 to 1.9, p=0.001, for FEV1/FVC ratio of 63 to 71.5, p=0.002). Conclusion: Community pharmacist based education program applied to patients with asthma to increase awareness of patients about proper inhaler technique have positive impact in improvement of asthma control level and pulmonary functions parameters. This short education program highly applicable and should be consider as one of daily community pharmacist duties. Keywords: Community pharmacist, asthma control test, asthmatic patients, spirometer, inhaler technique, Thi-Qar.